(untitled) (Biological Sciences - PJSIR, 2022)
intermingling growth with Alternaria solani and Aureobasidum pullulans with Cladosporium cladosporioides. Therefore, these arc least inhibitory. Highest inhibition zone was observed with A. terre us for both the pathogens. The maximum inhibition in. growth of these two test fungi was observed when grown with Aspergillus terreus and Trichoderma viridae. This may be in part due to production of some antifungal substances or may be due to spatial problem. A. terreus has been reported to produce antibiotics such as gcodin, terricin and terric acid [6]. These antibiotics might be providing inhibitions in the growth of the pathogenic fungi.